Zenon i Antemiusz w jednym stali domu czyli o konflikcie sąsiedzkim w Konstantynopolu - Wolińska, Teresa (Vox Patrum, 2026)
The article discusses a dispute between two prominent inhabitants of Constantinople, Zeno the Rhetor and Anthemius of Tralles. Anthemius kept teasing his neighbour in a very particular way, by a forced fake earthquake, made with steam boilers, as well as by using mirrors and resonating devices to simulate storms. Although the story may appear invented at first sight, a deeper analysis of the only source from which it is known, i.e. History by Agathias Scholasticus, as well as taking a closer look at Anthemius’ written works may suggest that the events described may have happened indeed. Anthemius is known mainly as the designer of Hagia Sophia. Yet, he was also a mathematician and engineer, familiar with the works of ancient scholars, such as Heron of Alexandria, Apollonius of Perga and Diocles. He himself wrote several treatises. He seems to have had enough knowledge and skills to haunt Zeno in the manner described, taking revenge for a lost court case. It seems likely that he wanted to test shock resistance of the building at the same time. Thanks to that he was a recognized expert on quakes, which he could artificially induce. Agathias, who himself experienced an earthquake, was skeptical to that. The description of the dispute between Zeno and Anthemius allowed him to show his erudition and to portray a symbolic clash between the legal and rhetorical knowledge on the one hand and the technical skills on the other.